PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TEHADAP KEPUASAN NASABAH DALAM MENGGUNAKAN BYOND BSI (STUDI PADA MAHAISWA UIN RADEN INTAN LAMPUNG PENGGUNA E BANKING BSI): indonesia - Zen Maulana Ihsan; Kurniawan , Muhammad; Kurniawan, Agus (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This research aims to determine the effect of service quality and product quality on customer satisfaction with the E-Banking Byond BSI product in a study of Uin Raden Intan Lampung students. This study uses a quantitative approach with data collection through questionnaires involving 100 respondents. The analysis results show that service quality has a positive and significant effect on customer satisfaction, with a p-value of 0.000. Product quality also has a positive and significant effect on customer satisfaction, with a p-value of 0.015. These findings indicate that the better the quality of service provided by Byon BSI and the more credible the services offered to customers, the greater the customer satisfaction in using the Byond BSI application. These two variables are interrelated; the quality of the product and the quality of the service have a very close relationship with customer satisfaction.